Multivariate analysis of factors related to academic performance in nursing - Aguilar-Restor, Nerissa
Nursing has evolved into a discipline that upholds academic excellence. Student achievement is therefore, a significant phenomenon. As research proved that academic performance is a function of several variables, this study investigated the academic and non-academic factors associated with students' performance in nursing. Such could facilitate clear understanding of academic achievement. This study was conducted among 1,364 third and fourth year nursing students of Far Eastern University in the academic year 2004-2005. Surveys and focus group discussions with respondents were done. The study described respondents' demographic, academic, familial, social and personal profiles after which, relationship of these variables with academic performance were determined using Chi square test (X2) and Pearson's correlation coefficient (r). Analysis of Variance (ANOVA) and cross tabulations were utilized to infer differences among students. Findings showed that third and fourth year nursing students are generally a normal population in terms of academic achievement. 16 percent of them were achievers, 71 percent were average and 13 percent underachievers. They were predominantly female, living in dormitories, graduates of private high schools, found theoretical aspect of nursing difficult and average performers in the Nursing Aptitude Test (NAT). Their parents are mostly college graduates although only majority of the fathers are working. More than fifty percent reported not having steady girlfriends/boyfriends, and generally are active, visual, sensing and sequential learner. Findings showed these variables to be significantly associated with academic achievement. Statistical tests generated, gender ( X2 =61.23, p<0.001), people students live with (X2 =86.06, p=0.001), nature of high school (X2=83.71, p<0.001), aspect of nursing found difficult (X2=93.75, p<0.001), NAT scores (r = -.46, p<0.001), father's education (X2=446.14, p<0.001), mother's education (X2=619.82, p<0.001), steady girlfriend/boyfriend (X2=16.88, p<0.001), persons who motivated students to take nursing (X2=37.70, p<0.001) active (X2=10.57, p<0.001), sensing (X2=147.84, p<0.001), visual (X2=59.36, p<0.001), and sequential learning (X2=37.70, p<0.001) were significantly associated with academic performance. Significant differences existed among students in their NAT scores (F=2.52, p<0.012) habits. Teacher-student relationship did not have association with academic performance. However, majority of respondents obtained scores denoting fairly positive relationship with their teachers. In conclusion, academic performance in nursing is a function of several variables. Likewise, NAT is inversely related to academic performance. Moreover, students perceive their teachers to be generally competent but distant and not very approachable. General recommendations include maintaining close mentoring of students and revisiting the NAT to optimize learning.